Unravelling haematopoietic stem cell dysfunction in isolated Del(5q) myelodysplastic syndromes - Stenson, L (2015)
Myelodysplastic syndromes (MDS) represent a heterogeneous group of haematological malignancies. A subgroup of MDS patients are characterized by heterozygous deletion of the long arm of chromosome 5, Del(5q), as the only karyotypic abnormality. The commonly deleted region (CDR) on chromosome 5 contains approximately forty-two genes and haploinsufficiency of one or more of these genes is thought to be the basis for Del(5q) MDS pathogenesis. The 5q deletion originates in the Hematopoietic Stem Cell (HSC) compartment and Del(5q) HSCs have a clonal advantage, outcompeting healthy HSCs in the bone marrow of patients. Although they have a competitive advantage in situ, Del(5q) HSCs perform poorly in functional stem cell assays in vitro and in vivo. A mouse model of Del(5q) MDS, the Cd74-Nid67 model, carries a heterozygous deletion of eight genes located within the CDR. Cd74-Nid67 haploinsufficiency causes macrocytic anaemia and bone marrow dysplasia in mice. However, the impact of Cd74-Nid67 haploinsufficiency on HSC function has not previously been investigated. The results presented, herein, demonstrate that haploinsufficiency of Cd74-Nid67 has a significant impact on HSC self-renewal and repopulation potential. Furthermore, two genes within this region, Rps14 and Rbm22, are identified as likely candidates responsible for Cd74-Nid67 HSC dysfunction. Finally, we demonstrate that Cd74-Nid67 HSC dysfunction is driven by a P53-dependent mechanism. This study provides important insights into the mechanistic basis for disease development and propagation, which may facilitate the development of improved therapeutic avenues for Del(5q) MDS patients.